Outcomes Of Endoscopic Urethrotomy and Urethroplasty On Uretheral Strictures - Muhammad, Raza; Chandio, Mumtaz Ali; Akhtar, Syed Muhammad Hassan; Nawaz, Usama; Talha, Hafiz Usama; Inam, Qazi Adil (Journal of Neonatal Surgery, 2025)
Background: A small percentage of males get urethral stricture. As a first line of defence, urethrotomy is performed. A little over half of the strictures come back within four years. Repeat urethrotomy or open urethroplasty are two options for further therapy. Objective: The purpose of this research is to find out how well endoscopic urethrotomy and urethroplasty work for treating uretheral strictures. Methods: This retrospective analysis included 110 male patients underwent for uretheral stricture. Group I had 55 patients who got urethroplasty, whereas group II had 55 who received endoscopic urethrotomy. All patients in both groups were followed for 4-6 months. Both groups were compared for post-treatment success and complications. All data was analysed with SPSS 24.0. Results: The mean age of the patients in group I was 47.18±6.53 years and in group II was 50.14±11.78 years.Most common symptoms were dysuria, urinary retention and pollakiuria among both groups. Infection was the most common cause followed by urethral trauma. Membranous urethra strictures were most prevalent. A substantial difference in Q max flowmetry was seen between the two techniques after surgery (p-value <0.05). Postoperative success rate was higher in group I compared to group II (p < 0.004). Group II 11 (20%) had a greater recurrence rate than group I 4 (7.3%). Conclusion: In this study, we determined that urethroplasty is a safer and more effective procedure than endoscopic urethrotomy. Additionally, urethroplasty results in increased urine flow and an incidence of recurrence that is lower